Self-Formation of Superhydrophobic Surfaces through Interfacial Energy Engineering between Liquids and Particles - Yasmeen, Sumaira; Yoon, Jaehong; Moon, Chan Hui; Khan, Rizwan; Gaiji, Houda; Shin, Sangwoo; Oh, Il Kwon; Lee, Han Bo Ram (Langmuir, 2021)
The superhydrophobic surface has been used in ultradry surface applications, such as the maritime industry, windshields, non-sticky surfaces, anti-icing surfaces, self-cleaning surfaces, and so forth. However, one of the main hurdles for the production of superhydrophobic surfaces is high-cost fabrication methods. Here, we report a handy process of self-synthesis fabrication of superhydrophobic surfaces with daily supplies. Driven by the physics of biscuit dunking, we introduce a method to self-synthesize superhydrophobic surfaces from daily supplies by coating a substrate with a liquid (liquids of paraffin from candles or polydimethylsiloxane) and subsequently sprinkling powders (food-desiccant silica, alumina, sugar, salt, or flour). A mechanistic study revealed that the capillary force, governed by surface energy difference, liquid viscosity, and powder pore size, draws the liquid solution into the porous channels within the powders. The entire surface of powders, in turn, is covered with the low-surface-energy liquid to maintain the porosity, creating a 3D porous nanostructure, resulting in a water contact angle over 160°. This work provides a scientific understanding that technological developments are closely related to the science that can be seen in our daily lives. Also, we believe that further intensive studies extended from this work could enable to home-fabricate a superhydrophobic surface, such as a bathtub and sink in bathrooms and a cooking area and sink in kitchens.
Keywords: 3D porous nanostructures; Low surface energy; Mechanistic studies; Super-hydrophobic surfaces; Surface applications; Surface energy differences; Technological development; Water contact angle